iTRAQ-Based Proteomic Analysis of Dentate Gyrus in Temporal Lobe Epilepsy With Hippocampal Sclerosis - Xiao, Wenbiao; Yang, Zhiquan; Yan, Xiaoxin; Feng, Li; Long, Lili; Tu, Tian; Deng, Na; Chen, Wenjuan; Xiao, Bo; Long, Hongyu; Zeng, Yi (Frontiers in Neurology, 2021)
Temporal lobe epilepsy (TLE) is the most frequent type of focal epilepsy in adults, typically resistant to pharmacological treatment and mostly present with cognitive impairment and psychiatric comorbidities. The most common neuropathological hallmark in TLE patients is hippocampal sclerosis (HS). However, the underlying molecular mechanisms involved remain poorly characterized. Dentate gyrus (DG), one specific hippocampal subarea, structural and functional changes imply a key involvement of the DG in the development of TLE. In this study, isobaric tags for relative and absolute quantitation (iTRAQ) -based quantitative proteomic technique was performed to the analysis of hippocampal DG obtained from patients with TLE-HS compared to control samples obtained from the autopsy. Our proteomic data identified 5583 proteins, of which 82 proteins were up-regulated and 90 proteins were down-regulated. Bioinformatics analysis indicated that differential expressed proteins enriched in “synaptic vesicle”, “mitochondrion”, “cell-cell adhesion”, “regulation of synaptic plasticity”, “ATP binding” and “Oxidative phosphorylation”. Protein-protein interaction network analysis found a pivotal module of 10 proteins that were related to “Oxidative phosphorylation”. This study has investigated proteomic alterations in DG region of TLE-HS patients, and paved the way to the better understanding of epileptogenesis mechanisms and the future therapeutic intervention.